Systematic analysis of virus nucleic acid sensor DDX58 in malignant tumor - Huang, Zhijian; Yi, Limu; Jin, Liangzi; Chen, Jian; Han, Yuanyuan; Zhang, Yan; Shi, Libin (Frontiers in Microbiology, 2022)
Abstract: In December 2019, a novel epidemic of coronavirus pneumonia (COVID-19) was reported，and population-based studies had shown that cancer was a risk factor for death from COVID-19 infection. However, the molecular mechanism between COVID-19 and cancer remains indistinct. In this paper, we analyzed the nucleic acid sensor (DDX58) of SARS-CoV-2 virus, which is a significant gene related to virus infection. For purpose of clarifying the characteristics of DDX58 expression in malignant tumors, this study began to systematically analyze the DDX58 expression profile in the entire cancer type spectrum. Using TCGA pan-cancer database and related data resources, we analyzed the expression, survival analysis, methylation expression, mutation status, microsatellite instability (MSI), immune related microenvironment, gene related network, function and drug sensitivity of DDX58. The expression level of DDX58 mRNA in most cancers was higher than the expression level in normal tissues. Through TIMER algorithm mining, we found that DDX58 expression was closely related to various levels of immune infiltration in pan-cancer. The promoter methylation level of DDX58 was significantly increased in multiple cancers. In addition, abnormal expression of DDX58 was related to MSI and TMB in multiple cancers, and the most common type of genomic mutation was “mutation”. In the protein-protein interaction (PPI) network, we found that type I interferon, phagocytosis, ubiquitinase, and tumor pathways were significantly enriched. Finally, according to the expression of DDX58 indicated potential sensitive drugs such as Cediranib, VE−821, Itraconazole, JNJ−42756493, IWR−1, and Linsitinib. In conclusion, we had gained new insights into how DDX58 might contribute to tumor development, and DDX58 could be used as an immune-related biomarker and as a potential immunotherapeutic target for COVID-19 infected cancer patients.